Motional Dynamics of Halogen‐Bonded Complexes Probed by Low‐Field NMR Relaxometry and Overhauser Dynamic Nuclear Polarization - Banerjee, Abhishek; Dey, Arnab; Chandrakumar, N. (Chemistry, an Asian journal, 2019)
Halogen bonding is a subject of considerable interest owing to wide‐ranging chemical, materials and biological applications. The motional dynamics of halogen‐bonded complexes play a pivotal role in comprehending the nature of the halogen‐bonding interaction. However, not many attempts appear to have been made to shed light on the dynamical characteristics of halogen‐bonded species. For the first time, we demonstrate here that the combination of low‐field NMR relaxometry and Overhauser dynamic nuclear polarization (ODNP) makes it possible to obtain a cogent picture of the motional dynamics of halogen‐bonded species. We discuss here the advantages of this combined approach. Low‐field relaxometry allows us to infer the hydrodynamic radius and rotational correlation time, whereas ODNP probes the molecular translational correlation times (involving the substrate as well as the organic radical) with high sensitivity at low field. It′s a perfect combination! The combination of low‐field NMR relaxometry and Overhauser dynamic nuclear polarization (ODNP) enabled the characterization of the motional correlation times of halogen‐bonded species and inference of the respective molecular volumes.